ACNUC: a nucleic acid sequence data base and analysis system. - Gouy, M (1984)
Structured as a data base and associated with data analysis tools, ACNUC allows both on-line access to a central computer and local exploitation of published nucleotide sequences. Its data retrieval capabilities seem to be presently the most powerful available.